Acute myeloid leukemia is associated with retroviral gene transfer to hematopoietic progenitor cells in a rhesus macaque - Seggewiss, Ruth (The American Society of Hematology, 2006)
We report, for the first time, a replication-defective retroviral vector–associated neoplasia in a nonhuman primate. Five years after transplantation with CD34(+) cells transduced with a retroviral vector expressing enhanced green fluorescent protein (eGFP) and a drug-resistant variant of the dihydrofolate reductase gene (L22Y), a rhesus macaque developed a fatal myeloid sarcoma, a type of acute myeloid leukemia. Tumor cells contained 2 clonal vector insertions. One insertion was found in BCL2-A1, an antiapoptotic gene. This event suggests that currently available retroviral vectors may have long-term side effects, particularly in hematopoietic stem and progenitor cells.